Giant aneurysm of the splenic artery (Bangladesh Medical Journal Khulna, 2022)
Splenic artery aneurysms (SAA) are one of the common visceral aneurysms. However giant SAA have barely been reported. We discuss a case of SAA, who had prior history of caroli disease at the stage of secondary biliary cirrhosis for which he was a candidate for liver transplantation. The patient underwent open surgical repair. The proximal and distal spenic artery were ligated from within the aneurysm and surgery was completed with splenectomy. The post operative period was uneventful.Bang Med J Khulna 2021; 54 : 26-27